RECENT STUdIES Of BIOEThICS ANd ThE NEEd ThAT ThE BUSINESSMEN TO ASSUME ThE CORPORATE SOCIAl RESPONSIBIlITy - Trujillo Meza, Julio César (2012)
Fundamentally, the subject matter is a motivational analysis in respect to the objectives of the Companies and of the institutions over which should take into account the need for further consideration of the Ethics and Bioethics, like criteria and standards of behavior for better result in economic management and success of the Companies. While the backgrounds of the application of bioethics have a starting point in the medicine, it is also true, that has been studied quite the application of ethics and bioethics in the business sector who to apply its principles have improved their production and sales activity. Particularly, they have improved all related environment, being recognized by society. The researches up to date that has been derived to the companies, about bioethical reasoning, seems be good and valid in their application as be refl cted in the study which show rates, dimensions and positive criteria showing that all companies and activities that include and consider bioethical reasoning, are able to improve their results and the image of the company actually show an improvement in their corporate social responsibility with remarkable success. I believe that the University should disseminate this knowledge as a new mission applicable to all sectors of the economy to improve and they are considered socially responsible companies and mostly successful.